A Novel Biological Role of α‐Mangostin in Modulating Inflammatory Response Through the Activation of SIRT‐1 Signaling Pathway. Issue 11 (4th April 2016) - Franceschelli, Sara; Pesce, Mirko; Ferrone, Alessio; Patruno, Antonia; Pasqualone, Livia; Carlucci, Giuseppe; Ferrone, Vincenzo; Carlucci, Maura; de Lutiis, Maria Anna; Grilli, Alfredo; Felaco, Mario; Speranza, Lorenza
Abstract : Several studies have shown that xanthones obtained from Garcinia Mangostana ( GM) have remarkable biological activities. α‐mangostin (α‐MG) is the main constituent of the fruit hull of the GM. Several findings have suggested that SIRT‐1, a nuclear histone deacetylase, could influence cellular function by the inhibition of NF‐kB signaling. ROS can inhibit SIRT‐1 activity by initiating oxidative modifications on its cysteine residues, and suppression of SIRT‐1 enhances the NF‐κB signaling resulting in inflammatory responses. The goals of the present study were to evaluate the quantity of α‐MG in the methanolic extract of GM (Vithagroup Spa) and to investigate the activity of this xanthone in U937 cell line and in human monocytes from responsive to inflammatory insult analyzing the possible changes on the activation of SIRT‐1 protein via NF‐Kb. Cells were treated with the methanolic extract of GM and/or LPS. The chromatographic separation of α‐MG was performed by an HPLC analysis. EX 527, a specific SIRT‐1 inhibitor, was used to determine if SIRT‐1/NfkB signaling pathway might be involved in α‐MG action on cells. Our results show that α‐MG inhibits p65 acetylation and down‐regulates the pro‐inflammatory gene products as COX‐2, iNOS via SIRT‐1 activation. Cells treated with EX 527 showed an up‐regulation of NFkB acetylation and an over expression of inducible enzymes and their product of catalysis (NO and PGE2). These results suggest that α‐MG may be useful for the development of alternative pharmacological strategies aimed at reducing the inflammatory process. J. Cell. Physiol. 231: 2439–2451, 2016. © 2016 Wiley Periodicals, Inc.